An activatable fluorescent probe with an ultrafast response and large Stokes shift for live cell bioimaging of hypochlorous acid. Issue 109 (11th November 2016) - Liu, Feng; Tang, Ying; Kuang, Yongqing; Pan, Dan; Liu, Xianjun; Yu, Ru-Qin; Jiang, Jian-Hui
Abstract : A novel "turn-on" fluorescent probe for high selectivity, rapid detection and imaging of HOCl based on the protection of carbaldehyde with 2-mercaptoethanol. Abstract : A novel activatable fluorescent probe for hypochlorous acid (HOCl) imaging, has been developed based on HOCl-triggered aldehyde recovery reaction. This probe features with a long emission wavelength because of the use of intramolecular charge transfer (ICT) effect in the fluorophore. Moreover, this probe displayed ultrafast response (within 1 s), good selectivity and high sensitivity (detection limit of 50 nm) toward HOCl with excellent independency upon pH of the assay system. Live cells imaging studies demonstrate that the probe can be applied successfully to detect exogenous and endogenous HOCl.